Empowering Students in Increasing Knowledge of Geometry Concepts - Alberth Supriyanto Manurung; Abdul Halim (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
This community service activity is carried out with the aim of increasing knowledge through the concept of geometry, namely to increase knowledge about flat shapes and spaces that change every time. The subject of community service is 30 students at SDN Jakarta. The activity begins with preparations in the form of socialization at the location where the activity will be carried out to provide an explanation of the activities to be carried out. At the activity implementation stage, students were gathered in a room to listen to material presentation on geometric concepts. Then the implementation team conducted counseling and demonstrations on arithmetic material. The instructor conducts an evaluation in the form of questions and answers to the participants during the extension. Based on the evaluation of the activity, there has been an increase in knowledge about geometry material, students after counseling and demonstrations on how to solve geometry material problems correctly. Students who have knowledge of geometric concepts increased from those who were initially able to answer 5 questions out of 15 questions to 10 questions out of 15 questions with an increase in answering questions above 60%. Furthermore, we, as the implementing team, suggest that counseling be carried out routinely to different targets, namely students who have not received counseling, as well as the same target for refreshment and re-evaluation. Counseling or training also needs to be carried out with the target teacher, so that trained teachers can convey it back to their students.